2015
DOI: 10.1186/s12939-015-0169-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of social support and social networks in health information–seeking behavior among Korean Americans: a qualitative study

Abstract: IntroductionThis study used social network theory to explore the role of social support and social networks in health information–seeking behavior among Korean American (KA) adults.MethodsA descriptive qualitative study using a web-based online survey was conducted from January 2013 to April 2013 in the U.S. The survey included open-ended questions about health information–seeking experiences in personal social networks and their importance in KA adults. Themes emerging from a constant comparative analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 48 publications
5
90
1
2
Order By: Relevance
“…We believe African community organizations in the city could act as knowledge broker organizations that could link service providers with immigrant communities [19, 48]. Knowledge broker organizations and social networks can be useful at developing connections between network members for supporting immigrants to access services and develop cultural competence within the health care system [48, 49]. The research team members believe the development of mentorship programs would especially be of value.…”
Section: Discussionmentioning
confidence: 99%
“…We believe African community organizations in the city could act as knowledge broker organizations that could link service providers with immigrant communities [19, 48]. Knowledge broker organizations and social networks can be useful at developing connections between network members for supporting immigrants to access services and develop cultural competence within the health care system [48, 49]. The research team members believe the development of mentorship programs would especially be of value.…”
Section: Discussionmentioning
confidence: 99%
“…Acceptability of the HPV vaccine was also found to be highest when “when people believed that important others wanted them to be vaccinated or held favorable beliefs toward the vaccine” [40]. Social network theory as applied to public health is a means by which knowledge of and attitudes towards a health behavior can be formed [41]. In this case, the use of bed nets may be influenced by the individuals whom the pregnant women seek advice from during their pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…When examining the use of information resources by older people looking for health information, prior studies have found that the most significant sources of medical information are family and social networks (Kim, Irwin, Kim, Chin & Kim, 2015;Kim, Kreps & Shin, 2015;Makris, Abrams, Gurland & Reid, 2014;P alsd ottir, 2014). Therefore, looking for medical information relies to a great extent on the social connectedness of the searcher (Fox & Jones, 2009).…”
Section: Health Literacy Among Older Peoplementioning
confidence: 99%